Developing Visual Word Book Media Integrated with Structural Synthetic Analytics (SAS) Method in Improving Elementary School Students’ Early Reading Skills - Musyarofah, Musta'inatul; Purwati, Panca Dewi (Journal of Language and Literature Studies, 2026)
Reading comprehension is a basic skill for lower grade students as a foundation for further learning. The students at Elementary schools in Semarang still have difficulty recognizing the letters ‘b, d, and p’, so appropriate learning media are needed to support their early reading skills.  This study aims to describe the design of the Visual Word Book learning media development assisted by the SAS method, reveal the results of validation tests conducted by experts, and test the effectiveness of the developed media in improving the early reading skills of first-grade elementary school students. This study used the RnD method with the Borg and Gall model, which was implemented in eight of ten stages. The research subjects consisted of first-grade students and teachers at SDN Plumutan Kab Semarang. Data collection techniques in this study included observation, interviews, questionnaires, as well as pre-tests and post-tests. Data analysis was performed using normality tests, paired sample t-tests, and N-Gain tests. The results showed that the development of the Visual Word Book media, designed based on the SAS method stages, was deemed highly feasible, with media experts scoring 97% and subject matter experts scoring 95% in the validation results. In addition, the effectiveness test results showed an improvement in early reading skills among first-grade elementary school students, as indicated by N-Gain scores in the moderate category. Thus, the Visual Word Book media assisted by the SAS method is effective and feasible for use as an early reading learning medium.